Reviewing soil carbon sequestration for assessing the potential of Indian agriculture - Choudhury, Shreyasi Gupta (Indian Farming, 2015)
A fundamental understanding of the dynamics of C stock in soils as influenced by management strategies is necessary to evaluate the pathways of C sequestration in soils. Different agro-ecological regions with varying soil types and cropping systems may play the pivotal role in the long-term accumulation and sequestration of atmospheric C and that is very much important to maintain soil organic C (SOC) at a level critical for upkeeping soil health. Enrichment of C stock in soils has dual effect on maintaining soil health for sustainable production and global food security vis-a-vis curbing global warming. This is more important in tropical, subtropical, arid and semi-arid regions where soils are inherently low in organic C content and production system is fragile. A much higher C saturation deficit may encourage the soil to credit C and to build the potential for C trading with countries having higher C saturation level. Different conservation strategies and management practices have a significant effect on soil carbon sequestration under Indian sub continental condition.